ANALISIS USER EXPERIENCE JOGJAKITA MENGGUNAKAN USER EXPERIENCE QUESTIONNAIRE (UEQ) - Prayoga, Aditya; C W Kusuma; M Christy; R Andika (Badan Penelitian dan Pengabdian Masyarakat (BP2M) STMIK Syaikh Zainuddin NW Anjani, 2023)
This analysis is influenced by the rapid growth of information and communication technologies, which has a major impact on the environment of society and changes the way people live and work. User experience is becoming increasingly important in increasing the effectiveness of an application and strengthening the relationship between user and application. However, the use of applications also has significant impacts on the community’s environment, including increased energy consumption and related environmental impacts. Therefore, it is important to evaluate the impact of the use of applications/internet and user experience on the community environment. Yogyakarta, which is one of the largest cities in Indonesia with several tourist locations in every district and village center, is the right place to do such an evaluation. Most measurements using UEQ have positive values, on the sixth UEQ scale (Attractiveness, Perspicuity, Efficiency, Dependability, Stimulation and Novelty), only the percentage value on the aspect of innovation in these applications needs to be improved again and reevaluated.